A gas-sensing array produced from screen-printed, zeolite-modified chromium titanate. (10th July 2015) - Pugh, David C; Hailes, Stephen M V; Parkin, Ivan P
Abstract: Metal oxide semiconducting (MOS) gas sensors represent a cheap, robust and sensitive technology for detecting volatile organic compounds. MOS sensors have consistently been shown to lack sensitivity to a broad range on analytes, leading to false positive errors. In this study an array of five chromium titanate (CTO) thick-film sensors were produced. These were modified by incorporating a range of zeolites, namely β, Y, mordenite and ZSM5, into the bulk sensor material. Sensors were exposed to three common reducing gases, namely acetone, ethanol and toluene, and a machine learning technique was applied to differentiate between the different gases. All sensors produced strong resistive responses (increases in resistance) and a support vector machine (SVM) was able to classify the data to a high degree of selectivity.